REVITALIZATION OF BEACH TOURISM AREA THROUGH INTEGRATED WASTE CLEANUP MOVEMENT FOR ENVIRONMENTAL SUSTAINABILITY, CASE STUDY: TIRANG ISLAND - Muhammad Yusuf Pratama; Luthfan Nursyamsul Ahfi; Alfin Isy Ni’mah; Naqiyatuz Zakia; Muhammad Nabil Amjad; Khusnul Mariah; Hardiansyah Tri Bima; Mutma’inah Mutma’inah (MIMBAR INTEGRITAS : Jurnal Pengabdian, 2025)
Humans are consumers who depend on natural products and the environment, but human awareness in maintaining and preserving nature is still very low. This research is a form of service and uses a participatory approach that involves elements of the community and the management of tourist attractions. The activity was carried out by observation and then continued with 3 stages of activity, namely program socialization, beach clean-up action and waste management system education. This research is aimed at educating the community in protecting the environment and pouring it into a real movement. This research contributed significantly in revitalizing the condition of Tirang beach from full of garbage to clean again with a sustainable waste management system run by the local community.